2019
DOI: 10.9734/ajeba/2019/v13i130164
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Procurement Practices on Service Delivery: A Case Study of VRA, Ghana

Abstract: This study was conducted to determine the effect of procurement policy, procurement planning and sustainable procurement on service delivery. The study employed a quantitative research approach and explanatory design. The target population for the study was staff and management of the Volta River Authority. Structured questionnaire was used to gather primary data. The study used SPSS version 32.0 for the data analyses. The study found that 73.6% variations in service delivery were explained by Procurement Poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
4
12
0
Order By: Relevance
“…The study finds that procurement planning has a positive and significant effect on the procurement performance of tertiary institutions. This confirms earlier work by [15], who studied the effect of procurement practices on the procurement quality of public sugar manufacturing firms in Western Kenya and reported a positive and negligible impact on procurement efficiency. It also provides support to [16] who concludes that procurement planning enhances supplier's performance in service delivery.…”
Section: The Effect Of Procurement Planning On Procurement Performancesupporting
confidence: 90%
“…The study finds that procurement planning has a positive and significant effect on the procurement performance of tertiary institutions. This confirms earlier work by [15], who studied the effect of procurement practices on the procurement quality of public sugar manufacturing firms in Western Kenya and reported a positive and negligible impact on procurement efficiency. It also provides support to [16] who concludes that procurement planning enhances supplier's performance in service delivery.…”
Section: The Effect Of Procurement Planning On Procurement Performancesupporting
confidence: 90%
“…This finding has been supported by previous empirical studies (Van Weele and Van Raaij, 2014; Torabi et al. , 2018; Anane et al. , 2019) which concluded that exposure to procurement process risk leads to project failure and performance issues arising from poor product specifications, poor supplier selection and procurement delays.…”
Section: Discussionsupporting
confidence: 72%
“…For example, public organizations can receive goods, works and services for day-to-day operations through public procurement. Also, the public can access services provided by the government through effective public procurement practices in public organizations (Abioro, 2021;Anane et al, 2019;Basheka, 2021). For instance, governments can procure health equipment and medicines to enhance health service delivery to the public (Adusei, 2018;Israel et al, 2019;Miller and Lehoux, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, public organizations can receive goods, works and services for day-to-day operations through public procurement. Also, the public can access services provided by the government through effective public procurement practices in public organizations (Abioro, 2021; Anane et al. , 2019; Basheka, 2021).…”
Section: Introductionmentioning
confidence: 99%